1999
DOI: 10.1103/physreve.59.826
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic growth of field-oriented chains in dipolar colloidal solutions

Abstract: Experimental studies on the irreversible growth of field-induced chains of dipolar particles suggest an asymptotic power-law behavior of several relevant quantities. We introduce a Monte Carlo model of chain growth that explicitly incorporates the anisotropic diffusion characteristic of a rodlike object. Assuming a simple power-law form for the mean cluster size S(t)ϳt z , the results of our model are in good agreement with the experimental measurements of the dynamic exponent z. Nevertheless, an alternative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 24 publications
2
26
1
Order By: Relevance
“…28 It should be stressed that the dynamical scaling property of anisotropic two-dimensional systems during coarsening processes has been reported by several authors and demonstrated by computer simulations performed under confined conditions, i.e., in very thin layers or in slab geometries with thicknesses similar to the values of the characteristic correlation distance ͓R͑t͒ =2 / q 1 ͔ in the plane. [31][32][33][34][35] Geometrical confinement effects were not expected in the samples studied here because the film thicknesses ͑Ϸ200 nm͒ are about ten times the largest R͑t͒ values derived from our SAXS curves. Therefore, the present study reveals the validity of the dynamic scaling hypothesis in intrinsic bidimensional coarsening processes.…”
Section: Resultsmentioning
confidence: 84%
“…28 It should be stressed that the dynamical scaling property of anisotropic two-dimensional systems during coarsening processes has been reported by several authors and demonstrated by computer simulations performed under confined conditions, i.e., in very thin layers or in slab geometries with thicknesses similar to the values of the characteristic correlation distance ͓R͑t͒ =2 / q 1 ͔ in the plane. [31][32][33][34][35] Geometrical confinement effects were not expected in the samples studied here because the film thicknesses ͑Ϸ200 nm͒ are about ten times the largest R͑t͒ values derived from our SAXS curves. Therefore, the present study reveals the validity of the dynamic scaling hypothesis in intrinsic bidimensional coarsening processes.…”
Section: Resultsmentioning
confidence: 84%
“…The cluster diffusion coefficients do not depend on the direction in which the clusters move, i.e., hydrodynamic corrections are not important as they are in case of constant magnetic fields (author?) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless this model takes into account that the force between two aggregates depends on their respective size and also that the average distance between aggregates increases during the aggregation process. Several numerical simulations have focused on the exponent of the growth of the chain average size l with time: l(t) ∝ t α and have found α between 0.5 and 0.7; the last limit corresponds to the case where dipolar forces dominate Brownian forces [3,4]. A detailed analysis of the power law exponents was carried out both by Brownian dynamics simulation and experimentally, for large box sizes with energy of the dipole-dipole interaction of the particles being between two and three order of magnitude larger than the thermal energy kT [5].…”
Section: Introductionmentioning
confidence: 99%